Pengaruh Strategi Pemasaran, Kompetensi SDM, Pengelolaan Keuangan dan Sistem Informasi Akuntansi Dalam Meningkatkan Kinerja UMKM - Indriyani, Dini; Gunawan Aji; Amalia Karimah; Pipit Fitriani; Isna Amaliya (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
UMKM have an important role in improving the economic sector in Indonesia. Increasing economic growth will also have an impact on the progress and welfare of business people or UMKM. The purpose of this study was to explore the influence of marketing strategy, human resource competence (HR), financial management and accounting information systems in improving the performance of UMKM. This study uses qualitative research methods by analyzing theory and the influence or relationship between the dependent and independent variables quoted from journals sourced from Google Scholar. This study shows that marketing strategy, human resource competence (HR), financial management, and accounting information systems (SIA) have a positive effect on the performance of UMKM.